How we learn learning and non-learning in school and beyond - Illeris, Knud (Routledge, 2007)
Deals with the fundamental issues of the processes of learning, critically assessing different types of learning and obstacles to learning. This book provides a comprehensive introduction to both traditional learning theory and the international research into learning processes.